Who expects to join criminal gangs and why? Occupational choice among 5,000 teenage boys in Medellín (2024)
Across the Americas, criminal gangs are among the largest forced recruiters of children and adolescents into armed groups. What techniques do they use? Which adolescents are most at risk? And what NGO and government interventions can prevent and disrupt this forced recruitment? We are currently running a survey targeting 5,000 13-year-old adolescent males in Medellin’s highest-risk gang recruitment neighborhoods. We will use the survey to assess risk factors associated with recruitment. To mitigate the identification problem concerning the separation of preferences, expectations, and structural barriers, we use rich data on subjective expectations, with direct measures of financial constraints, to estimate a life-cycle model of preferred career path. In this preliminary paper, we describe the model, report preliminary descriptive statistics, and discuss intervention design. By May, we expect to present descriptive statistics on the full sample and report results of survey experiments that will inform our field experimental interventions.